A PERTUMBUHAN DAN KUALITAS NUTRISi INDIGOFERA ZOLLINGERIANA PADA TANAH MARJINAL DAN INOKULUM MIKORIZASEBAGAI PAKAN TERNAK KERBAU RAWA: Tanaman dan ternak - laksono, judo; Hermanto, Hermanto; Agustina, Syintia Dwi; Sumini, Sumini (Agrienvi: Jurnal Ilmu Pertanian, 2023)
This study aims to determine how the growth and quality of Indigofera plants on marginal soils with the help of Arbuscular Mycorrhizal Fungi biofertilizer. This research will be carried out at the Animal Husbandry Experimental Garden, Faculty of Agriculture, Musi Rawas University, to analyze the quality of nutrition will be tested in the Laboratory of Nutrition and Animal Feed, Faculty of Animal Husbandry, Jambi University. Each treatment unit was repeated 4 times, so the total number of experimental units was 24 experimental units. The treatment factors are as follows: M0 = Tanpa Mikoriza M1 = 5 gr Mikoriza / polybag M2 = 10 gr Mikoriza / polybag M3 = 15 gr Mikoriza / polybag M4 = 20 gr Mikoriza / polybag M5 = 25 gr Mikoriza / polybag analyzed using analysis of variance (ANOVA), if there is a significant difference between treatments, the Least Significant Difference (BNT) test will be carried out. From the analysis of the growth variance of Indigofera zollingeriana and Mycorrhizal Inoculum on marginal soil as animal feed, it significantly (P<0.05) had a significant effect (P<0.05) on the parameters of plant height, number of petioles, stem diameter, root length and biomass weight. Based on the results of the research above, it can be concluded that the provision of arbuscular mycorrhizae can increase the growth and production of Indigofera zollingeriana plants.